2018
DOI: 10.1126/sciadv.aat2390
|View full text |Cite
|
Sign up to set email alerts
|

A general printing approach for scalable growth of perovskite single-crystal films

Abstract: A seed printing method is developed for controllably producing perovskite single-crystal films with high yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(172 citation statements)
references
References 39 publications
6
166
0
Order By: Relevance
“…Apart from continuous thin films, single‐crystal perovskite arrayed films are also appealing for many optoelectronic applications, such as luminous pixel matrices in panel displays, and photodetector microarrays in camera modules . Gu et al introduced an ordered‐perovskite seed stamp into the space‐confined solvent evaporation crystallization process, which significantly inhibited random nucleation and enabled the scalable growth of various single‐crystal perovskite thin film arrays with millimeter‐sizes and controllable thicknesses from hundreds of nanometers to more than 10 μm (Figure e). To prepare the perovskite seed array, perovskite inks were inkjet printed onto a fluorosilane‐functionalized silicon wafer, and the ordered perovskite seeds were then formed as the droplets evaporated.…”
Section: Fabrication Methods For Perovskite Single‐crystal Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from continuous thin films, single‐crystal perovskite arrayed films are also appealing for many optoelectronic applications, such as luminous pixel matrices in panel displays, and photodetector microarrays in camera modules . Gu et al introduced an ordered‐perovskite seed stamp into the space‐confined solvent evaporation crystallization process, which significantly inhibited random nucleation and enabled the scalable growth of various single‐crystal perovskite thin film arrays with millimeter‐sizes and controllable thicknesses from hundreds of nanometers to more than 10 μm (Figure e). To prepare the perovskite seed array, perovskite inks were inkjet printed onto a fluorosilane‐functionalized silicon wafer, and the ordered perovskite seeds were then formed as the droplets evaporated.…”
Section: Fabrication Methods For Perovskite Single‐crystal Thin Filmsmentioning
confidence: 99%
“…In addition, single‐crystal MAPbI 3 photodetectors with a similar structure were also fabricated, and led to a similar performance . Of particular note is that massive photodetector arrays on large‐area single‐crystal perovskite wafers have promising potential applications as image sensors, as demonstrated by Gu et al (Figure e–h).…”
Section: Applications Of Single‐crystal Perovskite Thin Filmsmentioning
confidence: 99%
“…To selectively grow CsPbBr 3 microplate arrays in the vapor phase, we first fabricated CsPbBr 3 seeds on silicon using our previously reported inkjet printing method. [ 24 ] Inkjet printing technology is a facile method that can selectively deposit traces of semiconductor materials in large scale. [ 25,26 ] Consequently, a dilute perovskite precursor solution was printed on a silicon wafer to prepare the CsPbBr 3 seeds with the desired patterns.…”
Section: Figurementioning
confidence: 99%
“…However, chemical solution methods process with imperfect surface coverage and pinholes generated in large-area perovskite thin films fabrication, which seriously influences the solar cell's stability and efficiency [13][14][15][16]. Gu et al [17] reported a facile seed printing method to produce a millimeter-scale perovskite single crystal film with controlled thickness and high yield through a printing process. This further proves that the perovskite single crystal film can be directly printed.…”
Section: Introductionmentioning
confidence: 99%